2014
DOI: 10.1186/1476-4598-13-201
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone-induced conformational changes of PAK1 interrupt prosurvival MEK-ERK signaling in colorectal cancer

Abstract: BackgroundThymoquinone (TQ) was shown to reduce tumor growth in several cancer models both in vitro and in vivo. So far only a few targets of TQ, including protein kinases have been identified. Considering that kinases are promising candidates for targeted anticancer therapy, we studied the complex kinase network regulated by TQ.MethodsNovel kinase targets influenced by TQ were revealed by in silico analysis of peptide array data obtained from TQ-treated HCT116wt cells. Western blotting and kinase activity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ERK1/2 acts as nearly 180 different molecules targets and regulates several diverse cellular functions such as cell growth, cell cycle, proliferation, cell death, cell apoptosis, cell adhesion and transcription [9]. In fact, the ERK1/2 plays the above roles in various cancers, such as breast cancer [10], colorectal cancer [11], prostate cancer [12] and lung cancer [13]. However, not all references support the role of activated ERKs in promoting tumorigenesis, and result consistent with the role in tumor suppression has been reported as well [14].…”
Section: Introductionmentioning
confidence: 98%
“…Since then, increasing numbers of studies have focused on TQ in cancer therapy. Numerous in vitro and in vivo studies have investigated the antitumor activity of TQ in several types of cancer (6,14,19,(27)(28)(29)33). In tumor protein p53-null myeloblastic leukemia HL-60 cells, TQ induced apoptosis through an intrinsic signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that TQ exerted an antitumor effect through the interruption of pro-survival mitogen-activated protein kinase kinase 7-mitogen-activated protein kinase 1 signaling in colorectal cancer (14). TQ exerted a direct antitumor effect, and also sensitized cancer cells to other therapies (23,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation